Dynamic versus fixed cerebral perfusion pressure targets in paediatric traumatic brain injury: a STARSHIP analysisResearch in context - C.A. Smith; S.Y. Bögli; M.M. Placek; M. Cabeleira; D. White; E. Daubney; A. Young; E. Beqiri; R. Kayani; R. O'Donnell; N. Pathan; S. Watson; et al. (EClinicalMedicine)
Summary: Background: Cerebral perfusion pressure (CPP) represents a key target for intensive care management of paediatric traumatic brain injury (TBI) patients. Current guidelines recommend a CPP target within the range of 40–50 mmHg but emphasise that these may depend on patient age and the state of cerebrovascular autoregulation. In this analysis, we aimed to compare the fixed targets proposed by the Brain Trauma Foundation to autoregulation-based targets CPPopt (optimal CPP) and LLA (Lower Limit of Autoregulation). Methods: Data were acquired from the STARSHIP study (a prospective, multicentre, observational, research study which enrolled 135 children (median age 96 months (interquartile range 26–152 months)) with TBI between July 2018 and March 2023 across 10 paediatric intensive care units in the UK). In this secondary analysis the dose or percentage time spent below a fixed CPP target of 50 mmHg or CPPopt or LLA (assessed continuously on a minute-by-minute basis and derived by fitting a curve to the relationship between CPP and pressure reactivity index values, as previously described) was compared by outcome using univariable and multivariable methods. ClinicalTrials.gov registration–NCT0688462. Findings: When assessed within ordinal analyses (to account for differences in baseline severity), both hourly dose and percentage time spent below LLA (odds ratio 1.01 [95% CI 1.00–1.02], p = 0.017 and 1.05 [95% CI 1.01–1.08], p = 0.008 respectively) were independently associated with worse outcomes. LLA displayed a dynamic time-trend increasing over time in patients with unfavourable outcome (n = 44, p = 0.003). Overall, LLA exceeded 50 mmHg for more than 45% of the monitoring period across all patients, and for over 35% of the time in the youngest cohort (0–2 years). Interpretation: Dynamic autoregulation monitoring based on LLA was associated with outcomes in paediatric TBI with higher LLA values observed in individuals experiencing unfavourable outcomes. Our findings indicate that the current fixed CPP threshold of 40–50 mmHg may be too low–highlighting the need for further investigation into autoregulation-guided CPP targets. Whether personalised management based on autoregulatory-informed thresholds offers advantages over guideline-based targets remains to be determined and should be investigated in future prospective interventional studies. Funding: Action Medical Research for Childrens' Charity and Addenbrookes Charitable Trust (UK Grant number–GN2609).